Comparative analysis of radical scavenging and immunomodulatory activities of Tinospora cordifolia growing with different supporting trees - Bhalerao, Bharat Muralidhar (Acta Biologica Szegediensis, 2012)
According to Ayurveda, Tinospora cordifolia (Willd.) Miers (Menispermaceae) growing with physical support of Azadirachta indica Juss. (Meliaceae) (Neem) is medicinally more active than that growing on other supporting trees. In present study, comparative evaluation of antioxidant and immunomodulatory activities of ethanol extracts of T. cordifolia growing with the support of four different trees.viz Azadirachta indica (TCA), Acacia leucophloea (Roxb.) Willd. (Fabaceae) (TCB), Butea monosperma (Lamb.) Taub. (Fabaceae) (TCC) and Prosopis juliflora (Sw) DC. (Fabaceae) (TCD) was done. Evaluation of immunomodulatory potential of the extracts at the dose of 200 mg/kg body weight was done in rats, whereas phytochemical profile was established by HPLC. In in vitro antioxidant potential, TCA showed the highest i) total phenol content (21.5 mg/g dry weight), ii) total anti-oxidant activity (2144 μM Fe (II)/g dry mass), iii) DPPH free radical scavenging (86.36%), and iv) anti-lipid peroxidation potential (96.8%). It also showed the highest (11.7%) neutrophil adhesion and 275% more reduction in paw edema volume over control in TCA treated rats in vivo immunomodulatory activity. Only in humoral immune response, TCD (4.66 HA units) was found to be superior over the rest three extracts. In HPLC profiles of the extracts, TCA showed the presence of one extra peak at 9.88 minutes.